The Impact of Quran Recitation Habits Before Class on Students’ Mental Readiness for Learning - Muhammad Kurnia Sandy Kurnia; Edi Suresman; Jenuri; Akhmad Roja Badrus Zaman (Journal of Islamic Education Research, 2024)
This study examines the impact of Quran recitation habits at the beginning of learning sessions on students’ mental readiness. Employing a quantitative approach and simple linear regression analysis, the research explores the relationship between Quran recitation and students’ preparedness for learning. A sample of 153 eleventh-grade students from SMAN 8 Bandung was selected through simple random sampling, with data collected via a closed-ended questionnaire assessing Quran recitation habits and mental readiness indicators. The findings reveal a significant positive relationship between Quran recitation and mental readiness, with an R-squared value of 0.556, indicating that 55.6% of the variance in mental readiness is accounted for by Quran recitation. These results underscore the potential of integrating spiritual practices, such as Quran recitation, into educational routines to enhance students’ focus and emotional preparedness, thereby fostering improved academic engagement.